A Comparison of the Electrochemical Oxidative Dissolution of Pyrite and Chalcopyrite in Dilute Nitric Acid Solution - Samaneh Teimouri; Johannes Herman Potgieter; Caren Billing (ChemistryOpen)
Abstract Understanding the oxidation of sulfidic minerals, especially those of pyrite and chalcopyrite, under acidic conditions has important outcomes, such as exposing any encapsulated gold not recovered by traditional cyanidation processes. This study focused on the electrochemical oxidation of pyrite and chalcopyrite in a 0.5 M nitric acid solution. Electrochemical techniques were employed, using the minerals as working electrodes. Cyclic voltammetry (CV) was performed to detect redox processes and resulting products were suggested. Electrochemical impedance spectroscopy (EIS) was run at specific potentials corresponding to oxidation processes detected to further probe the reaction mechanism. For pyrite at low anodic potentials (0.4–0.6 V vs Ag/AgCl), Fe1‐xS2 and Fe(OH)3 with a sulfur‐rich layer which forms S0 accumulates on the electrode surface, leading to diffusion controlled dissolution processes. Above 0.7 V, the pyrite is fully oxidised, eradicating the diffusion barrier and extensive oxidation occurs at high potentials (0.9 V). Similar processes occurred for chalcopyrite with mainly iron‐deficient sulfides (like Cu1‐xFe1‐yS2‐z, CuS2, CuS) forming at low potentials (0.3–0.5 V), and S0 partially covering the surface causing a diffusion barrier. Increasing the potential to beyond 0.7 V leads to these layers converting to soluble species.